Pulmonary amyloidosis as the presenting finding in a patient with multiple myeloma - Ryan Kronen; David R. Ziehr; Ashley E.D. Kane; Paul A. VanderLaan; Cyrus A. Kholdani; Robert W. Hallowell (Respiratory Medicine Case Reports, 2022)
We present the case of a 58-year-old man who presented with dyspnea, cough, and weight loss and was ultimately diagnosed with pulmonary amyloidosis and multiple myeloma. Diagnosis was achieved with a lung biopsy which showed AL amyloid deposits involving the interstitium, vessels, and airway. He was treated with cyclophosphamide, bortezomib, and dexamethasone but died prior to completing treatment. His case is unique for the amyloid deposition found in all three lung compartments with clear pathophysiologic manifestations of each compartment, and the rapid disease progression that led to respiratory failure and death.